Comparing the Efficacies of Electrospun ZnO and TiO2 Nanofibrous Interlayers for Electron Transport in Perovskite Solar Cells - Abdullah Zafar; Waqar Iqbal; Shahzaib Khan; Aiyeshah Alhodaib; Mahvish Fatima (Ceramics)
ZnO and TiO2 are both well-known electron transport materials. Their comparison of performance is considered advantageous and novel. Therefore, a viable electrospinning route was considered for the development of highly polycrystalline TiO2 and ZnO nanofibers as an electron transport material (ETM) for perovskite solar cells. The materials were well-characterized in terms of different analytical techniques. The X-ray diffraction detected polycrystalline structural properties corresponding to TiO2 and ZnO. Morphological analysis by scanning electron microscopy revealed that the nanofibers are long, uniform, and polycrystalline, having a diameter in the nanometer range. Optoelectronic properties showed that TiO2 and ZnO exhibit absorption values in the ultraviolet and visible ranges, and band gap values for TiO2 and ZnO were 3.3 and 3.2 eV, respectively. TiO2 bandgap and semiconductor nature were more compatible with Electron Transport Layer (ETL) compared to ZnO. Electrical studies revealed that TiO2 nanofibers have enhanced values of conductivity and sheet carrier mobility compared to ZnO nanofibers. Therefore, higher photovoltaic conversion efficiency was achieved for TiO2 nanofibers (10.4%) compared to ZnO (8.5%).